Film: Memperlicin Jalan Dakwah - Muhtadi, Asep Saeful (Prophetica, 2009)
Film can be catogerized as one of the many communications media because its function to deliver a message. Furthermore, of course film can be one of the most important media in dakwah activities. As a engineered audio-visual media, film can be a potential media to transform religious messages. Therefore, it is undoubtedly that the presence of film not only as solely entertainment, but also can be full of values message, in this case, dakwah Islam.